Assessment of Alpha-Tocopheryl Acetate and Metformin Hydrochloride as Independent Agents on Human Dermal Fibroblast Viability: Findings from MTT Assay - Alfarafisa, Nayla Majeda; Khairani, Astrid Feinisa; Achadiyani, Achadiyani; Chou, Yoan; Aulia, Fitri; Firdaus, Muhammad Bintang (Althea Medical Journal, 2025)
Background: Alpha-tocopheryl acetate (Vitamin E) and metformin hydrochloride have been tested as anti-aging compounds at various concentrations. This study aimed to identify the most effective concentrations of alpha-tocopheryl acetate and metformin hydrochloride in promoting the viability of human dermal fibroblasts (HDFs), a primary cell type in skin aging research.Methods: HDFs were isolated using a mechanical isolation method and cultured under standard conditions. Cells were treated with varying concentrations of alpha-tocopheryl acetate and metformin hydrochloride as independents agents. After 48 hours of incubation, cell viability was measured using the MTT assay.Results: Alpha-tocopheryl acetate had the highest HDF cell viability (107%) at a concentration of 50 μM. Metformin hydrochloride had the maximum HDF cell viability (158%) at 5 μM. However, the viability response varied across different concentrations for both agents, indicating that optimal dosing was essential for maximizing their effectiveness.Conclusions: Alpha-tocopheryl acetate at 50 μM and metformin hydrochloride at 50 μM yield the highest viability of HDFs in vitro. These findings suggest potential roles for both agents in anti-aging skin therapies. Further research is recommended to explore their mechanisms of action and to optimize dosing strategies for clinical applications.